Impact of oxidative stress defense on bacterial survival and morphological change in Campylobacter jejuni under aerobic conditions - Oh, Euna; McMullen, Lynn; Jeon, Byeonghwa (Frontiers in Microbiology, 2015)
Campylobacter jejuni, a microaerophilic foodborne pathogen, inescapably faces high oxygen tension during its transmission to humans. Thus, the ability of C. jejuni to survive under oxygen-rich conditions may significantly impact C. jejuni viability in food and food safety as well. In this study, we investigated the impact of oxidative stress resistance on the survival of C. jejuni under aerobic conditions by examining three mutants defective in key antioxidant genes, including ahpC, katA, and sodB. All the three mutants exhibited growth reduction under aerobic conditions compared to the wild type (WT), and the ahpC mutant showed the most significant growth defect. The CFU reduction in the mutants was recovered to the WT level by complementation. Higher levels of reactive oxygen species (ROS) were accumulated in C. jejuni under aerobic conditions than microaerobic conditions, and supplementation of culture media with an antioxidant recovered the growth of C. jejuni. The levels of lipid peroxidation and protein oxidation were significantly increased in the mutants compared to WT. Additionally, the mutants exhibited different morphological changes under aerobic conditions. The ahpC and katA mutants developed coccoid morphology by aeration, whereas the sodB mutant established elongated cellular morphology. Compared to microaerobic conditions, interestingly, aerobic culture conditions substantially induced the formation of coccoidal cells, and antioxidant treatment reduced the emergence of coccoid forms under aerobic conditions. The ATP concentrations and PMA-qPCR analysis supported that oxidative stress is a factor that induces the development of a viable-but-non-culturable (VBNC) state in C. jejuni. The findings in this study clearly demonstrated that oxidative stress resistance plays an important role in the survival and morphological changes of C. jejuni under aerobic conditions.